THE STUDY OF ATTACHMENT PROPERTIES OF GRAPE CROWN GALL AGENTS STRAINS - Н. В. Ліманська; А. М. Венгер; Є. Шуай; В. О. Iваниця (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2007)
The method of bacterial attachment properties study on plant tissues was modified. The adhesive properties of 13 Rhizobium vitis strains isolated from grape and vineyard soil, and of the R. radiobacter strain isolated from rose were studied. It was shown that the strains of pathogenic rhizobia had different levels of adhesiveness (from 690,0+40,0 to 0,9+0,1 CFU/mm2). The greatest number of pathogenic rhizobia cells attached to grape and rose tissues and the least number - to chrysanthemum and kalanhoe tissues.